Применение методов статистической физики для описания стационарного функционирования производственных систем - Демуцкий, Виктор Петрович; Пигнастый, Олег Михайлович; Ходусов, Валерий Дмитриевич; Азаренкова, М. Н. (Харківський національний університет ім. В. Н. Каразіна, 2006)
The mathematical model of economic - industrial systems with mass production is constructed. The state of the production system at any moment is set by a point in two-dimension phase space. The distribution function for a base product is introduced and for it, the equation being analogue of a rate equation in physics is noted. The engineering - industrial and generating functions are determined. In a zero approximation, the closed system of the equations for the moments of a distribution function is written. For a closed system of equations of state of macro parameters of an industrial system, the equations of a perturbed state are obtained. Stability conditions of operation of an industrial system are defined.
Application of methods of the statistical physics for the description of stationary operation of industrial systems
Keywords: синергетика; базовый продукт; микроскопическое описание; функция распределения; инженерно-производственная функция; генераторная функция; уравнения балансов; synergetics; base product; microscopic description; distribution function; engineering-production function; generating function; balances equations